STRATEGIC MANAGEMENT IN ENSURING ECONOMIC AND FINANCIAL STABILITY (American Journal of Interdisciplinary Research and Development, 2024)
This article presents the stages of strategic management in ensuring economic and financial stability, the purpose of strategic analysis. The stages of strategic selection and implementation of 5P strategy and several models of their application are highlighted.